IMAJI DAN IMAJINASI MOTIF HIAS LIMAN DAN DELIMA DALAM RANAH TRANSFORMASI DESAIN MASA PRA-ISLAM HINGGA MASA ISLAM PARA WALI DI KERATON CIREBON - Husen Hendriyana (Jurusan Seni Rupa ISBI Bandung, 2015)
The decorative motifs of Liman and Delima are parts of the cultural work of the past Cirebon Palace which are very unique, distinctive, and metaphorical. They have phonological imaginative and metaphorical appeals which finally constitute this research. It is not only the sound of the term symbol and the name of the artifact, but it is also the values and elements that support the realization behind the artifact. The phonological description which is reflected on a term of the work, and under the form of the work, certainly has a meaning that can be expressed in units of structure and scientific conceptions. Among others, from their language reflection, the images and imagination of the work can be understood through the analysis of structural-mythopoic, which employed interdisciplinary analysis method. Efforts to uncover the value and the meaning of both ideoplastis and visioplastis, tangible or intangible, are synonymous with the process to know what are the subjective and objective reality behind the work, and how the implied relationship values deals with the system and the expression of the culture of the people, especially on the creative traditional pattern–art in accordance with the facility era. Keywords: metaphorical logos, images and imagination, Liman and Delima Motifs of Cirebon___________________________________________________________Motif hias Liman dan Delima merupakan bagian karya budaya masa lalu Istana Cirebon yang unik, khas dan metaforis. Motif-motif ini memiliki daya tarik metaforis dan imajinatif fonologis yang akhirnya mendorong penelitian ini. Bukan hanya bunyi suatu simbol istilah dan nama suatu artefak tetapi juga nilai-nilai dan unsur-unsur yang melatarbelakangi pembuatan artefak. Deskripsi fonologis yang direfleksikan dalam istilah karya dan bentuk karya tentu memiliki makna yang dapat diungkapkan dalam unit-unit struktur dan konsepsi ilmiah. Di antaranya, dari refleksi bahasanya, imaji dan imajinasi karya dapat dipahami melalui analisa struktural-mythopoeia, menggunakan metode analisa lintas disiplin ilmu. Usaha-usaha untuk mengungkapkan nilai dan makna ideoplastis dan visioplastis, berwujud atau tidak berwujud, bersinonim dengan proses untuk mengetahui realitas objektif dan subjektif di balik karya, dan bagaimana nilai-nilai hubungan yang tersirat berkaitan dengan sistem dan ekspresi budaya masyarakat, khususnya dalam pola tradisional kreatif – seni yang sesuai dengan era kecakapan.Kata Kunci: Logos Metaforis, Imaji dan Imajinasi, Motif-motif Cirebon Liman dan Delima